2015
DOI: 10.1007/s11255-015-1011-3
|View full text |Cite
|
Sign up to set email alerts
|

Castration impairs erectile organ structure and function by inhibiting autophagy and promoting apoptosis of corpus cavernosum smooth muscle cells in rats

Abstract: Castration attenuates erectile function and induces corporeal fibrosis by inhibiting autophagy and promoting apoptosis of CCSMCs in rats. Therefore, our study highlights the important role of androgens in maintaining the integrity of the structure and function of corpus cavernosum in rats through counter-regulation of autophagy and apoptosis, mainly by regulating BECN 1-Bcl-2 interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Castration of rodent animal models results in reduced erectile function, as evidence by lowered development of intracorporal pressure following cavernous nerve stimulation [2529]. Several investigators have proposed that change in penile architecture is the main mediator of the effects of androgen deprivation which produces penile tissue atrophy concomitant with alterations in dorsal nerve structure, endothelial morphology, reduction in trabecular smooth muscle content, increased deposition of extracellular matrix and accumulation of fat-containing cells (adipocytes) in the sub-tunical region of the corpus cavernosum [3036]. The androgen-dependent loss of erectile response is restored by androgen administration where there is some evidence that the mechanism may involve differentiation of progenitor cells into smooth muscle cells and inhibition of their differentiation into adipocytes [28, 29, 35,3738].…”
Section: Role Of Testosterone In Cellular Physiology: John Mulhall Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Castration of rodent animal models results in reduced erectile function, as evidence by lowered development of intracorporal pressure following cavernous nerve stimulation [2529]. Several investigators have proposed that change in penile architecture is the main mediator of the effects of androgen deprivation which produces penile tissue atrophy concomitant with alterations in dorsal nerve structure, endothelial morphology, reduction in trabecular smooth muscle content, increased deposition of extracellular matrix and accumulation of fat-containing cells (adipocytes) in the sub-tunical region of the corpus cavernosum [3036]. The androgen-dependent loss of erectile response is restored by androgen administration where there is some evidence that the mechanism may involve differentiation of progenitor cells into smooth muscle cells and inhibition of their differentiation into adipocytes [28, 29, 35,3738].…”
Section: Role Of Testosterone In Cellular Physiology: John Mulhall Kmentioning
confidence: 99%
“…It has been shown that castration results in erectile dysfunction [31, 35] and reversibly alters corpora cavernosal architecture. Trabecular smooth muscle content decreases [29, 36] while connective tissue abundance increases [31, 36]. In addition, fat-containing cells accumulate in the corpora cavernosa [31], resulting from androgen deprivation effects on progenitor stromal cells causing them to differentiate into an adipogenic lineage [31].…”
Section: Testosterone Effects On Penile Development and Adult Penile mentioning
confidence: 99%
“…Autophagy has also been implicated in other animal models of ED. Wang et al showed that castration leads to ED and induced CC fibrosis by suppressing autophagy and enhancing apoptosis in rats CSMCs (Wang et al, 2015). Li et al demonstrated that autophagy is inhibited in a hyperlipidemia rat ED model, which was considered to be part of the pathogenic mechanism (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy also plays a significant role in age-related ED. Wang et al showed that castration leads to ED and induced CC fibrosis by suppressing autophagy and enhancing apoptosis in rats CSMCs (Wang et al, 2015). Moreover, autophagosome number is remarkably reduced in the CSMCs of aging rats.…”
Section: Figurementioning
confidence: 99%
“…Administration of PDE5-Is was shown to effectively prevent PL shortening (Berookhim et al, 2014;Montorsi et al, 2014), while preserved postoperative PL was shown to correlate well with the maintenance of erectile function after nerve-sparing RP (Briganti et al, 2007;Engel et al, 2011). One study utilizing a castrated animal model showed greater fibrosis and enhanced apoptosis of the penis tissues (Wang et al, 2015), while another reported internal pudendal artery dysfunction (Alves-Lopes et al, 2017). Despite varying widely, erectile function among our study population was generally poor.…”
Section: Discussionmentioning
confidence: 99%